(untitled) (Quest Journal of Management and Social Sciences, 2023)
Background: Understanding the elements and variables influencing a decision is crucial for making the best financial decisions possible. Investors make complex decisions using their instincts, perceptions, emotions, and thought processes. Objectives: This paper aims to examine the effect of market variables on investment decisions concerning the financial market of Nepal. Methods: The research used primary sources of data collected through structured questionnaires. The researchers have applied purposive sampling techniques and selected 168 respondents who have been involved in the transaction of the secondary financial market for at least one year in the Nepalese stock market. We used descriptive and explanatory research design, including correlation analysis and multiple linear regression model, to analyze the data with the help of statistical software. Results: Young people from a new generation are becoming an increasingly large portion of the capital market and are actively participating in the Nepali security market. The study finds that the stock’s price, customer preferences, past stock trends, and market information in the secondary market highly impacts investment decision. However, the company’s fundamental report has no significant impact on investment decisions in the secondary market. Conclusion: Investors need to understand the financial landscape of the country prior to investing. Policymakers should understand the behavior of investors to promote the secondary market, and proper market information should be disclosed that may help to make better investment decisions in the secondary market.